Production Capacity Optimization By Silica Crust Analysis “TB-001” and “TB-002” Wells Sorik Marapi Geothermal Field - Wahyuzar, Dirga (Journal of Petroleum and Geothermal Technology, 2025)
The Sorik Marapi located in Mandailing Natal Regency, North Sumatra. Silica scale production wells “TB-001” and “TB-002” makes pipe diameter smaller, inhibits fluid flow, reduces energy output, and increases cost of cleaning even replacing pipes. The research expected to produce efforts to prevent silica scale thus production capacity optimized. Method used is Silica Saturation Index (SSI) with amorphous and quartz silica types. Temperature and pressure are important where appropriate settings can minimize silica scale. Study focused on the wellhead and separator part of the well. Furthermore, comprehensive feasibility evaluation of production well was conducted. Cap rock smectite - hematite mineral about 20° - 240°C and reservoir illite - epidote mineral about 240° - 340°C. Geothermal fluid is dominated by chloride water. Both wells have the potential silica scale in separator with SSI >1 and not in wellhead with SSI<1. The treatment to prevent the silica scale is to use hydrofluoric acid (HF) solution with concentration of 15% and immersion time of 15 minutes, where the effectiveness value is about 46-47%. Keywords: Geothermal; Production Wells; Silica Crust; Sorik Marapi; SSI